Pengaruh Social Media Marketing dan Pengalaman Merek terhadap Niat Beli dengan Ekuitas Merek sebagai Variabel Mediasi Pada Kopi Fore - Rahmad Safrudin; Ari Anggarani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to examine the influence of social media marketing and brand experience on purchase intention through brand equity as a mediating variable in fore coffee. This research is motivated by increasing purchase intentions due to the use of social media identified as a key factor in influencing consumer perceptions of the Fore coffee brand. Additionally, brand experience is considered a factor that plays an important role in shaping brand equity, and ultimately motivating purchase intention. This research used respondents with the criteria of having or encountered content on Fore Coffee social media and knowing about Fore Coffee drinks in the Tangerang area. The sampling technique used in this research used a purposive sampling technique of 140 respondents using the SEM analysis method. The research results in this study show that social media marketing and brand experience have a positive effect on brand equity. Social media marketing and brand experience also have a positive effect on purchase intention. Brand equity also has a positive effect on purchase intention. Then, the social media marketing variable has a direct and positive effect on purchase intention through brand equity. The brand experience variable also has a direct and positive effect on purchase intention through brand equity. The managerial implication of this research on Fore Coffee is that marketing strategies via social media need to be improved to strengthen Fore Coffee brand equity. Managing brand experience well can improve consumer perception of the brand. Furthermore, increasing brand equity can be used as a focus to stimulate consumer purchasing intentions.